PENERAPAN METODE DECISION TREE ALGORITMA C4.5 UNTUK SELEKSI CALON PENERIMA BEASISWA TINGKAT UNIVERSITAS - Nadiya Hijriana; Muhammad Rasyidan (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2017)
Scholarship is an award of financial aid for a student to further their education where it usually provided by goverment or any private institution. One of the problems that arise in distribution of scholarship is how to select student who is really approriate to get scholarship. This research using Decision Tree Method from Algorithm C4.5 and RapidMiner 5.3 as software for making a model that it can be used as a tool to help making decision in selection’s process of scholarship recipients. Keywords: Scholarship, Selection, Decision Tree Method, C4.5 Algorithm